Different forms of hydrogen production: a review and future perspectives - Cristina de Araujo, Grazielle; Antonio Cruz Siqueira, Jair; Zanardini, Loreci; Felipe Peixoto Marques, João; Lazzarin, Rafaela; Julio Sakata, Allex (Latin American Journal of Energy Research, 2022)
There was a significant increase in the concern with climate issues, among them highlighted as the derivation of greenhouse gases from the burning fossil fuels, leading several research centers and researchers to seek new sources of less polluting energy, independent of the burn-based matrix of fuels. In this context, the present work has as main presenter a literature review, perspective and comparisons regarding the use of hydrogen as a clean energy source, presenting three main ways of obtaining it: a) through electrolysis using renewable sources; b) biohydrogen production, based on the photosynthesis of plants and algae; c) production through biodigesters.
Keywords: Hidrogênio verde, biohidrogênio, biocombustível, fontes renováveis, energia limpa